Spaceborne miniaturized UHF dual band helix antenna with a small frequency ratio. Issue 6 (23rd February 2021) - Xue, Kai; Liao, Shaowei; Zhu, Ruilong; Xue, Quan; Ding, Liqin; Wang, Yang; Guo, Qing
Abstract: This study proposes a novel miniaturized circularly polarized (CP) ultrahigh frequency (UHF) quadrifilar helix antenna for spaceborne applications. The dual‐band operation is realized using four inverted‐U shaped helical strips (IUSHSs) that are rotated and alternately arranged on the four faces of a hollow polyimide cuboid in a sequential rotation manner, which effectively reduces the size of the antenna. Furthermore, the four IUSHSs are connected by a cross‐shape strip at the top of the antenna to control the dual resonant frequencies, resulting in a small dual‐band frequency ratio. The proposed antenna is both lightweight and robust when compared with the conventional miniaturized CP antennas operating at similar bands with similar performance. In particular, its compact radiator provides effective miniaturized spaceborne solution without the need of high‐dielectric coefficient materials. A device for spaceborne application that operates at 402/505 MHz is designed, fabricated, measured, and in‐orbit tested with a weight of 651 g and an effective size of 0.161 × 0.161 × 0.228 λ 3 402MHz ( λ 402MHz is the wavelength at 402 MHz). The measured gain and axial ratio of the proposed antenna are better than 5.32 dBi and 2.18 dB, respectively, within 2 and 12 MHz bandwidth for the two bands. The test results proved that the methods used to design the proposed antenna are effective.